Social Media Use, Psychological Distress and Knowledge, Attitude, and Practices Regarding the COVID-19 Among a Sample of the Population of Pakistan - Rizwan, Muhammad; Ahmad, Tauseef; Qi, Xuehong; Murad, Manal Abdulaziz; Baig, Mukhtiar; Sagga, Abdullah Khalid; Tariq, Saba; Baig, Fizzah; Naz, Rozina; Hui, Jin (Frontiers in Medicine, 2021)
This study was conducted to assess social media (SM) use, psychological distress, and knowledge, attitude, and practices (KAP) regarding the coronavirus disease 2019 (COVID-19) among a sample of the population of Pakistan. A cross-sectional study was conducted in Multan, Pakistan between April and May 2020. Demographics details, SM use, psychological distress, and KAP on the COVID-19 were investigated. A total of 800 respondents were analyzed out of which 33.5% (n = 268) were women. No gender-wise difference was found in the terms of SM use and duration of SM use. Women were prone to have psychological disorders such as anxiety, depression, and stress than men in the current COVID-19 pandemic. The mean knowledge score of men was significantly higher compared to women (18.69 ± 4.20 vs. 16.89 ± 3.04, p < 0.001), while the mean score of the attitude and practices on the COVID-19 prevention measures was significantly better in women (p = 0.012 and p < 0.001, respectively). The psychological problems such as anxiety (p < 0.001) and depression scores (p = 0.033) were higher among women than men. The stress score was also higher in women but not significantly higher (p = 0.079). The knowledge was significantly correlated with attitude, anxiety, depression, and stress. The regression analysis showed that the COVID-19-related KAPs are the predictors of psychological suffering of an individual. The female gender was positively associated with anxiety and depression. The SM use was the predictor of the stress. Male respondents had significantly more knowledge of the COVID-19 than female respondents, but women had significantly better attitudes and practiced the COVID-19 prevention measures. Gender is a significant determinant of psychological distress and KAP about the COVID-19. The government has already taken significant steps to limit the spread of the disease; however, much more effort is required to tackle this COVID-19 pandemic.